Mg-Gd alloy with wide-temperature-range mechanical property improved through nano-particles and preparation method and application of Mg-Gd alloy

By introducing nano AlN ceramic particles into Mg-Gd alloy, the problems of decreased strength and insufficient plasticity of magnesium alloy at high temperatures are solved, and its mechanical properties are significantly improved, and its application range in aerospace and automobile manufacturing fields is expanded.

CN119243002AActive Publication Date: 2025-01-03CHONGQING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411445583.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-03
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The strength of magnesium alloys decreases at high temperatures, which cannot meet the needs of parts for use at high temperatures, and is weak in plasticity at low temperatures, limiting its application range.

Method used

By introducing nano AlN ceramic particles into Mg-Gd alloy, using them as α-Mg heteronucleation site to refine the alloy structure, improve the distribution of the Mg-Gd phase and play a role in strengthening the second phase, thereby improving the Mechanical properties of alloys.

Benefits of technology

It significantly improves the low-temperature, room-temperature and high-temperature mechanical properties of Mg-Gd alloy, enhances its tensile strength and yield strength, extends its application range, and is suitable for key components in the aerospace and automobile manufacturing fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243002A_ABST
    Figure CN119243002A_ABST
Patent Text Reader

Abstract

The invention discloses an Mg-Gd alloy with wide-temperature-range mechanical properties improved by nano-particles and a preparation method and application of the Mg-Gd alloy. The Mg-Gd alloy comprises the following components in percentage by mass: 10-12% of gadolinium; 0.3 to 1.0 wt.% of aluminum nitride; and the balance of magnesium. The magnesium is a mixture of pure magnesium and a magnesium-gadolinium intermediate alloy. According to the Mg-Gd alloy for improving the wide-temperature-range mechanical property through the nano-particles and the preparation method and application of the Mg-Gd alloy, the nano-AlN ceramic particles are introduced into a magnesium matrix by adding the nano-AlN / Mg intermediate alloy, and the nano-AlN particles serve as alpha-Mg heterogeneous nucleation sites to refine the alloy structure, improve the distribution of an Mg-Gd phase and play a role in strengthening a second phase, so that the mechanical property of the wide-temperature-range is improved, and the mechanical property of the wide-temperature-range is improved. Therefore, the mechanical property of the alloy is improved, and the application of the magnesium alloy as a key part in the fields of aerospace and automobile manufacturing is further expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-strength magnesium alloy preparation, and in particular to a Mg-Gd alloy with nanoparticles to enhance mechanical properties over a wide temperature range, and a preparation method and application thereof. Background Art

[0002] As the lightest alloy among the current metal structural materials, magnesium alloy not only has high specific strength and specific stiffness, but also has good vibration reduction performance. In the automotive field, magnesium alloy can significantly reduce the weight of objects and thus reduce energy consumption. Therefore, weight reduction through magnesium alloy materials has become an important trend in the automotive manufacturing industry. However, in low-temperature areas, the parts of automobiles have to withstand long periods of low or high temperatures during use. However, when the temperature exceeds 175°C, the strength of magnesium alloys will drop significantly, and it cannot meet the use requirements of parts at high temperatures. Therefore, the heat resistance of magnesium alloys needs to be improved.

[0003] Mg-RE alloy is a high-strength magnesium alloy system that is currently being studied and applied more frequently. Among them, Mg-Gd alloys have simple compositions and excellent high-temperature resistance, which can greatly reduce the weight of components in industrial production applications. However, at low temperatures, the plasticity of Mg-Gd alloys is average. When the temperature is higher than 200°C, the second phase still cannot effectively maintain the stability of the grain boundary, so the tensile strength of the alloy is weak, which greatly limits its scope of application. It is necessary to explore related processes to regulate the structure of Mg-Gd alloys and improve the performance of Mg-Gd alloys.

[0004] In the prior art, the mechanical properties of magnesium alloys can be improved by forming magnesium-based composite materials with external or internal particles, heat treatment, hot extrusion and other methods. Among them, AlN particles not only have the advantages of high melting point, high hardness, good thermal stability, etc., but also their crystal configuration and lattice parameters are similar to those of Mg, and are a reinforcing phase with great development potential in magnesium alloys. Therefore, introducing AlN particles into Mg-Gd alloys and studying the regulatory effect of AlN particles on the second phase structure and matrix grains of Mg-Gd alloys have important guiding significance and engineering application value for the development and application of high-strength magnesium alloys. Summary of the invention

[0005] The purpose of the present invention is to provide a Mg-Gd alloy with nanoparticles to improve the mechanical properties over a wide temperature range, a preparation method and an application thereof, wherein nano AlN ceramic particles are introduced into a magnesium matrix by adding a nano AlN / Mg master alloy. Nano AlN particles can serve as α-Mg heterogeneous nucleation sites to refine the alloy structure, improve the distribution of the Mg-Gd phase, and play a role in second phase strengthening, thereby improving the mechanical properties of the alloy, which is conducive to further expanding the application of magnesium rare earth alloys as key components in the fields of aerospace and automobile manufacturing.

[0006] To achieve the above object, the present invention provides a Mg-Gd alloy with nanoparticles to improve mechanical properties over a wide temperature range, comprising the following components in percentage by mass: Gadolinium 10~12wt.%; Aluminum nitride 0.3~1.0wt.%; The balance is magnesium; The magnesium is a mixture of pure magnesium and magnesium-gadolinium master alloy.

[0007] Preferably, the aluminum nitride is an AlN / Mg master alloy with a content of 40wt.% nano-AlN ceramic particles, the purity of the pure magnesium is 99.8%, and the magnesium-gadolinium master alloy is Mg-30wt.%Gd with a purity of 99.9%.

[0008] Preferably, the average size of the nano-AlN ceramic particles is 350 nm, and the diameter of the nano-AlN ceramic particles is 150-500 nm.

[0009] To achieve the above object, the present invention also provides a method for preparing a Mg-Gd alloy with nanoparticles to improve mechanical properties over a wide temperature range, comprising the following steps: S1. Raw material grinding: pure magnesium, magnesium-gadolinium master alloy and AlN / Mg master alloy are all ground; S2, alloy smelting: melting the polished pure magnesium obtained in S1 under the protection of a mixed gas, adding the polished magnesium-gadolinium master alloy obtained in S1 to melt under the protection of a mixed gas, and then adding the polished AlN / Mg master alloy obtained in S1 to melt under the protection of a mixed gas, and performing heat preservation stirring, slag removal, and casting to obtain an ingot; S3, homogenization treatment: homogenizing the ingot obtained in S2, and then air-cooling the treated ingot to room temperature to obtain an ingot; S4, extrusion treatment: hot-extrude the billet obtained in S3 to obtain an extruded rod.

[0010] Preferably, in S2, the mixed gas includes 99% by volume of CO2 and 1% by volume of SF6.

[0011] Preferably, in S2, the melting temperature of the pure magnesium is 710-730°C, the melting temperature of the magnesium-gadolinium master alloy is 700-720°C, and the melting temperature of the AlN / Mg master alloy is 790-800°C.

[0012] Preferably, in S2, the temperature of the heat preservation stirring is 780~800℃, and the heat preservation stirring is first mechanical stirring and then ultrasonic stirring; the stirring speed of the mechanical stirring is 50~100rpm and the stirring time is 5~7min, and the stirring frequency of the ultrasonic stirring is 19.5~20.7kHz and the stirring time is 3~5min.

[0013] Preferably, in S3, the temperature of the homogenization treatment is 520° C. and the time is 12 h.

[0014] Preferably, in S4, the hot extrusion temperature is 430° C. and the extrusion ratio is 18:1.

[0015] To achieve the above objectives, the present invention also provides a Mg-Gd alloy with nanoparticles to enhance mechanical properties over a wide temperature range for use as a key component in the aerospace and automobile manufacturing fields in the northern or southern polar regions.

[0016] Therefore, the present invention adopts the above-mentioned nanoparticles to improve the Mg-Gd alloy with wide temperature range mechanical properties, and the preparation method and application thereof, and the beneficial effects are as follows: (1) The present invention adds nano-AlN ceramic particles to the alloy. The nano-AlN ceramic particles have the characteristics of low density, high hardness, high melting point, etc., and can be introduced into the magnesium alloy to strengthen the alloy by hindering dislocation movement and grain boundary sliding. At the same time, the interface between the AlN ceramic particles and the Mg matrix is ​​clean and free of inclusions, and has a good lattice matching relationship with the magnesium matrix, which helps to reduce the size of α-Mg grains during the solidification process and improve the mechanical properties of the alloy.

[0017] (2) The present invention introduces mechanical stirring and ultrasonic stirring during the smelting process to promote the uniform dispersion of nano-AlN ceramic particles, thereby significantly strengthening the high-temperature properties of the alloy and improving the low-temperature plasticity.

[0018] (3) By adjusting the addition content of nano-AlN ceramic particles, the present invention found that the second phase structure in the alloy increased significantly, and the second phase structure was dispersed and evenly distributed in the grains. Under extrusion, when the addition amount of AlN was only 0.5wt.%, the yield strength and tensile strength of the composite material at -196℃, 25℃, and 250℃ were significantly higher than those of the Mg-Gd matrix alloy. Its low-temperature tensile properties had good strong plasticity and excellent high-temperature resistant mechanical properties, which significantly improved the low-temperature, room-temperature and high-temperature mechanical properties of the Mg-Gd alloy.

[0019] (4) The present invention can significantly improve the mechanical properties of Mg-Gd alloy by introducing low-content nano-AlN ceramic particles. The mechanical properties in a wide temperature range (-196~250℃) can be used not only in ordinary environments, but also in cold environments, such as the north and even the South and North Poles. The parts made of this material solve the problems of heat and overheating caused by high temperature and continuous working conditions, which leads to the degradation of material properties, and expands the application of magnesium alloys as key parts in the fields of aerospace and automobile manufacturing.

[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The figures are scanning electron microscope images of Mg-Gd alloys with improved wide temperature range mechanical properties by nanoparticles of the present invention, wherein (a) is a scanning electron microscope image of the Mg-12Gd matrix alloy prepared in Comparative Example 1, and (b) is a scanning electron microscope image of the 0.5wt.% AlN / Mg-12Gd alloy prepared in Example 2; Figure 2 This is the tensile engineering stress-strain curve of the 0.5wt.% AlN / Mg-12Gd alloy prepared in Example 2 of the Mg-Gd alloy with nanoparticles improving mechanical properties over a wide temperature range of the present invention. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0023] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0024] Embodiment 1 A Mg-Gd alloy with nanoparticles to improve mechanical properties in a wide temperature range comprises the following components in percentage by mass: 12 wt.% of gadolinium (Gd), 0.3 wt.% of aluminum nitride (AlN), and the balance of magnesium.

[0025] The preparation method comprises the following steps: S1. Raw material grinding: Pure magnesium, magnesium-gadolinium master alloy and AlN / Mg master alloy are all ground to remove surface stains and oxide scale to obtain ground pure magnesium, ground magnesium-gadolinium master alloy and ground AlN / Mg master alloy.

[0026] Among them, the purity of pure magnesium is 99.8%; the purity of magnesium-gadolinium master alloy (Mg-30wt.%Gd) is 99.9%, which is purchased from Chongqing Yuhua New Materials Technology Co., Ltd.; AlN / Mg master alloy (40wt.% AlN / Mg master alloy) contains 40wt.% nano AlN ceramic particles, and its preparation method is: Mg3N2 and pure aluminum powder with a mass ratio of 49.26:50.74 are ball milled, and then hot pressed and sintered. The ball milling speed is 280r / min; the ball-to-material ratio is 10:1; the hot pressing and sintering temperature is 1000℃. Among them, Mg3N2 is purchased from Shanghai Xiangtian Nanomaterial Co., Ltd., with a size of 2~8μm (average size of 5μm); pure aluminum powder is purchased from Beijing Xingrongyuan Technology Co., Ltd., with a size of 9~13μm (average size of 10μm) and a purity of 99.5%.

[0027] S2. Alloy smelting: the polished pure magnesium obtained in S1 is melted in a resistance furnace at a temperature of 720°C under the protection of a mixed gas, and then the polished magnesium-gadolinium master alloy obtained in S1 is added and melted again at a temperature of 700°C, and finally the polished AlN / Mg master alloy is added and melted again at a temperature of 800°C, and the mixture is kept warm and stirred at a temperature of 790°C. The stirring is first mechanically stirred (stirring speed is 50 rpm, stirring time is 5 min), and then ultrasonically stirred (ultrasonic frequency is 20.7 kHz, stirring time is 5 min); then the slag is removed, and finally casting is performed at a temperature of 700°C to obtain an ingot with a diameter of 85 mm.

[0028] Among them, the mixed gas is composed of 99% CO2 and 1% SF6 by volume; the mass ratio of pure magnesium in the ingot, the gadolinium content in the polished magnesium-gadolinium master alloy and the AlN content in the polished AlN / Mg master alloy is 87.7:12:0.3, and the diameter of the nano AlN ceramic particles is 150~500nm.

[0029] S3. Homogenization treatment: the ingot obtained in S2 is homogenized at 520° C. for 12 h, and the treated ingot is air-cooled to room temperature (25° C.) to obtain an ingot.

[0030] S4, extrusion treatment: the ingot obtained in S3 is hot extruded at a temperature of 430°C and an extrusion ratio of 18:1 to obtain an extruded rod with a diameter of 20 mm. The extruded rod is a nanoparticle reinforced Mg-Gd alloy, namely 0.3wt.% AlN / Mg-12Gd.

[0031] Embodiment 2 A Mg-Gd alloy with nanoparticles to improve mechanical properties in a wide temperature range comprises the following components in percentage by mass: 12 wt.% of gadolinium (Gd), 0.5 wt.% of aluminum nitride (AlN), and the balance of magnesium.

[0032] In this embodiment, the preparation method of the Mg-Gd alloy is exactly the same as the preparation method in the first embodiment, except that in the present embodiment S2, the mass ratio of pure magnesium in the ingot, the gadolinium content in the polished magnesium-gadolinium master alloy, and the AlN content in the polished AlN / Mg master alloy is 87.5:12:0.5, and the diameter of the nano-AlN ceramic particles is 150-500 nm. The alloy material finally obtained is 0.5wt.% AlN / Mg-12Gd.

[0033] Embodiment 3 A Mg-Gd alloy with nanoparticles to improve mechanical properties in a wide temperature range comprises the following components in percentage by mass: 12 wt.% of gadolinium (Gd), 1.0 wt.% of aluminum nitride (AlN), and the balance of magnesium.

[0034] In this embodiment, the preparation method of the Mg-Gd alloy is exactly the same as the preparation method in the first embodiment, except that in the present embodiment S2, the mass ratio of pure magnesium in the ingot, the gadolinium content in the polished magnesium-gadolinium master alloy, and the AlN content in the polished AlN / Mg master alloy is 87:12:1, and the diameter of the nano-AlN ceramic particles is 150-500 nm. The alloy material finally obtained is 1.0wt.% AlN / Mg-12Gd.

[0035] Comparative Example 1 This comparative example is a Mg-12Gd matrix alloy, which includes the following components in mass percentage: 12 wt.% of gadolinium (Gd), and the balance of magnesium.

[0036] The preparation method comprises the following steps: S1. Raw material grinding: Pure magnesium and magnesium-gadolinium master alloy are both ground to remove surface stains and oxide scales to obtain ground pure magnesium and ground magnesium-gadolinium master alloy.

[0037] Among them, the purity of pure magnesium is 99.8%; the purity of magnesium-gadolinium intermediate alloy (Mg-30wt.%Gd) is 99.9%, which is purchased from Chongqing Yuhua New Materials Technology Co., Ltd.

[0038] S2. Alloy smelting: The polished pure magnesium obtained in S1 is melted in a resistance furnace at a temperature of 720° C. under the protection of a mixed gas, and then the polished magnesium-gadolinium intermediate alloy obtained in S1 is added and melted again at a temperature of 720° C., and kept warm for 10 minutes, stirred to remove slag, and finally cast at a temperature of 700° C. to obtain an ingot with a diameter of 85 mm.

[0039] The mixed gas is composed of 99% by volume CO2 and 1% by volume SF6; the mass ratio of the pure magnesium in the ingot and the gadolinium content in the polished magnesium-gadolinium intermediate alloy is 88:12.

[0040] S3. Homogenization treatment: the ingot obtained in S2 is homogenized at a temperature of 520° C. for 12 h. The ingot after homogenization treatment is air-cooled to room temperature (25° C.) to obtain an ingot.

[0041] S4. Extrusion treatment: The ingot obtained in S3 is hot extruded at a temperature of 430° C. with an extrusion ratio of 18:1 to obtain an extruded rod with a diameter of 20 mm, and the extruded rod is a Mg-12Gd alloy.

[0042] Experimental Testing The structure and performance of the alloy materials prepared in Examples 1 to 3 and Comparative Example 1 were analyzed.

[0043] Microstructure analysis like Figure 1 As shown, Figure 1 (a) is a scanning electron microscope image of the extruded Mg-12Gd matrix alloy prepared in Comparative Example 1. Figure 1 (b) is a scanning electron microscope image of the extruded 0.5wt.% AlN / Mg-12Gd alloy of Example 2. With the introduction of nano-AlN ceramic particles, it can be observed that the volume fraction of micrometer-scale granular Mg rare earth-rich phase in the alloy increases and is more evenly distributed.

[0044] Mechanical properties test By conducting low temperature, room temperature and high temperature tensile property tests on the alloy prepared in Example 2, the tensile yield strength, tensile strength and fracture strain results are shown in Table 1.

[0045] Table 1 Performance test of extruded alloy at different temperatures

[0046] Figure 2 % AlN / Mg-12Gd alloy prepared in Example 2 at different temperatures.

[0047] According to Table 1, compared with the room temperature yield strength and tensile strength of the 0.5wt.% AlN / Mg-12Gd alloy prepared in Example 2, its yield strength and tensile strength at a low temperature of -196°C are increased by 101MPa and 156MPa respectively, but its elongation is only reduced by 3.2%; its yield strength at 250°C is only reduced by 6MPa, and its tensile strength is only reduced by 17MPa, but its elongation is increased by 9.4%; This shows that the nano-AlN ceramic particles effectively improve the plasticity of the alloy while ensuring the strength of the Mg-Gd alloy, so that it has excellent strength and plasticity at low and high temperatures.

[0048] Therefore, the present invention adopts the above-mentioned nanoparticles to improve the Mg-Gd alloy with wide temperature range mechanical properties, and the preparation method and application thereof. Nano AlN ceramic particles are introduced into the magnesium matrix by adding nano AlN / Mg master alloy. The nano AlN particles can serve as α-Mg heterogeneous nucleation sites to refine the alloy structure, improve the distribution of Mg-Gd phase, and play a role of second phase strengthening, thereby improving the mechanical properties of the alloy, which is conducive to further expanding the application of magnesium rare earth alloys as key components in the fields of aerospace and automobile manufacturing.

[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. Mg-Gd alloy with nanoparticles to improve mechanical properties over a wide temperature range, characterized in that: The following components are included in mass percentage: Gadolinium 10~12wt.%; Aluminum nitride 0.3~1.0wt.%; The balance is magnesium; The magnesium is a mixture of pure magnesium and magnesium-gadolinium master alloy.

2. The Mg-Gd alloy with nanoparticles improving mechanical properties over a wide temperature range according to claim 1, characterized in that: The aluminum nitride is an AlN / Mg master alloy with a content of 40 wt.% of nano-AlN ceramic particles, the purity of the pure magnesium is 99.8%, and the magnesium-gadolinium master alloy is Mg-30 wt.% Gd with a purity of 99.9%.

3. The Mg-Gd alloy with nanoparticles improving mechanical properties over a wide temperature range according to claim 2, characterized in that: The average size of the nano-AlN ceramic particles is 350 nm, and the diameter of the nano-AlN ceramic particles is 150-500 nm.

4. A method for preparing a Mg-Gd alloy with nanoparticles improving mechanical properties over a wide temperature range as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Raw material grinding: pure magnesium, magnesium-gadolinium master alloy and AlN / Mg master alloy are all ground; S2, alloy smelting: melting the polished pure magnesium obtained in S1 under the protection of a mixed gas, adding the polished magnesium-gadolinium master alloy obtained in S1 to melt under the protection of a mixed gas, and then adding the polished AlN / Mg master alloy obtained in S1 to melt under the protection of a mixed gas, and performing heat preservation stirring, slag removal, and casting to obtain an ingot; S3, homogenization treatment: homogenizing the ingot obtained in S2, and then air-cooling the treated ingot to room temperature to obtain an ingot; S4, extrusion treatment: hot-extrude the billet obtained in S3 to obtain an extruded rod.

5. The method for preparing a Mg-Gd alloy with nanoparticles improving mechanical properties over a wide temperature range according to claim 4, characterized in that: In S2, the mixed gas includes 99% by volume of CO2 and 1% by volume of SF6.

6. The method for preparing a Mg-Gd alloy with nanoparticles improving mechanical properties over a wide temperature range according to claim 4, characterized in that: In S2, the melting temperature of the pure magnesium is 710-730°C, the melting temperature of the magnesium-gadolinium master alloy is 700-720°C, and the melting temperature of the AlN / Mg master alloy is 790-800°C.

7. The method for preparing a Mg-Gd alloy with nanoparticles improving mechanical properties over a wide temperature range according to claim 4, characterized in that: In S2, the temperature of the heat preservation stirring is 780~800℃, and the heat preservation stirring is first mechanical stirring and then ultrasonic stirring; the stirring speed of the mechanical stirring is 50~100rpm and the stirring time is 5~7min, and the stirring frequency of the ultrasonic stirring is 19.5~20.7kHz and the stirring time is 3~5min.

8. The method for preparing a Mg-Gd alloy with nanoparticles improving mechanical properties over a wide temperature range according to claim 4, characterized in that: In S3, the homogenization treatment is performed at a temperature of 520° C. for 12 hours.

9. The method for preparing a Mg-Gd alloy with nanoparticles improving mechanical properties over a wide temperature range according to claim 4, characterized in that: In S4, the hot extrusion temperature is 430° C. and the extrusion ratio is 18:

1.

10. An application of a Mg-Gd alloy with nanoparticles as claimed in any one of claims 1 to 3 to enhance mechanical properties over a wide temperature range as a key component in the aerospace and automobile manufacturing fields in the northern or southern polar regions.

Citation Information

Patent Citations

  • AlN / Al particle reinforced magnesium aluminum rare earth based composite material and preparation method thereof

    CN114277277A

  • Magnesium-based composite material with improved heat resistance and preparation method thereof

    CN114277297A

  • AlN / AE44 composite material with excellent high-temperature mechanical property and preparation method thereof

    CN115976384A

  • Method for improving agglomeration of micron-sized AlN particles in magnesium-rare earth-based composite material

    CN117230341A